The Proportionality Principle: A Key to Fair Licensing Agreements - Umar, Wahyudi; Sudirman, Sudirman; Rasmuddin, Rasmuddin (Media of Law and Sharia, 2025)
This study examines the implementation of the principle of proportionality in license agreement clauses, focusing on how this principle can support fairness in the contractual relationship between grantees and licensees. In the era of globalization, licensing agreements are an essential tool in regulating intellectual property rights (IPR). Still, there is often an imbalance between the rights and obligations of the parties that can lead to disputes. The principle of proportionality ensures that each provision in the agreement reflects a fair balance, prevents exploitation of one party, and promotes a harmonious relationship. The research method used is normative legal research with a statutory and conceptual approach, which examines various licensing agreement clauses in Indonesia and their impact on the rights and obligations of the parties. The study results show that applying the principle of proportionality in licensing agreements can substantially increase fairness and reduce potential conflicts. Recommendations were given for the drafting of fairer and more sustainable licensing agreements, as well as the development of agreement law in Indonesia.